2021
DOI: 10.3389/fpsyt.2021.585589
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of Attention Deficits in the Social Problems and Withdrawn Behavior of Children With Sluggish Cognitive Tempo Symptoms

Abstract: Previous studies have found that sluggish cognitive tempo (SCT) symptoms are often associated with social problems and withdrawn behavior. However, the possible neuropsychological mechanism underlying this relationship remains unclear. Some studies have also found that SCT symptoms are related to deficits in sustained attention and selective attention. However, no study has examined whether attention deficits are related to social problems and withdrawn behavior in children with SCT. This study was the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…Omission errors in sustained attention task have been found to be positively associated with social problems and withdrawn behavior that are commonly present in children with high-SCT symptoms ( Yung et al, 2021 ). The results of the current study provide new evidence to explain the linkage between sustained attention difficulty and social problems/withdrawn behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Omission errors in sustained attention task have been found to be positively associated with social problems and withdrawn behavior that are commonly present in children with high-SCT symptoms ( Yung et al, 2021 ). The results of the current study provide new evidence to explain the linkage between sustained attention difficulty and social problems/withdrawn behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, why are youth with CDS socially disengaged? Although preliminary findings point to attention deficits as one potential mechanism (Yung et al, 2021), a large body of literature in developmental psychopathology on predictors, types, and outcomes of social withdrawal in youth has advanced separately from literature on CDS. Thus, to enhance our assessment and intervention of social withdrawal in youth with CDS, the following sections review and integrate findings on social withdrawal in order to advance a conceptual model of key mechanisms and moderators to further understand the CDS and social withdrawal link.…”
Section: Limitations Of the Literature And Need For A Conceptual Modelmentioning
confidence: 99%
“…Despite the consistent support for effects of CDS on social withdrawal, only one study, to our knowledge, has explored mechanisms or predictors of social withdrawal in individuals with CDS. In a community-based sample of school-aged children, task-based deficits in sustained attention were associated with greater parent-reported social withdrawal in children high in SCT (Yung et al, 2021).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…These phenotypes may correspond to the clinical setting where children after brain injuries often present with both attention-deficit hyperactivity disorder and social behavior problems ( 93 , 94 ). Recent studies have suggested that aberrant social behaviors may be attributed, at least in part, to deficits in sustained attention and attentional control ( 95 ). As such the relationship between social functioning and attention in pediatric TBI warrants further investigation, with potential implications for novel therapeutic targeting of both comorbidities.…”
Section: Modulating Secondary Injury Processes: Neuroinflammation and Oxidative Stressmentioning
confidence: 99%